Characterization and Optimization of Capryol-90, Polysorbate-80, And Peg-400 Proportion in Mefenamic Acid Self Nanoemulsifying Drug Delivery System (SNEDDS) With Simplex-Lattice-Design - Mardiyanto Mardiyanto; Najma Annuria Fithri; Martina Tandry (Science and Technology Indonesia, 2018)
Mefenamic acid as pain relief drug belongs to the biopharmaceutics classification system (BCS) class II which is practically insoluble in water causing extremely low dissolution in gastrointestinal tract. The self nanoemulsifying drug delivery system (SNEDDS) is a new innovation pharmaceutical dosage form that has effectively known to increase solubilization of hydrophobic drug in polar solvent. In this study the capryol-90 was selected as oil phase in SNEDDS as it showed maximal solubility of mefenamic acid (20 mg/mL). Combination of polysorbate-80 and PEG-400 as a generally regarded as safe (GRAS) excipient were used as surfactant and co-surfactant in SNEDDS due to its high HLB property that can increase mefenamic acid solubility in water. The ternary phase diagram of capryol-90, polysorbate-80, and PEG-400 was constructed in advance to obtain the component concentration of spontaneous nanoemulsion region. Model simplex-lattice-design cooperated in Design-Expert®10 was used to define SNEDDS mefenamic acid formula. Optimized mefenamic acid SNEDDS formula consisted of 20% capryol-90, 31.62% polysorbate-80, and 48.38% PEG-400. Characterization study of Optimized mefenamic acid SNEDDS formula showed improvement of drug content (102.820 ± 4.950)%, emulsification time (421.015 ± 1.290) second, and viscosity (0.927 ± 0.017) mm2/s 30oC. One way ANOVA statistical analysis result of optimal formula SNEDDS (105.210 ± 4.425)% of drug content, commercial generic caplet (0.917 ± 0.094)%, and mefenamic acid powder capsule (10.446 ± 0,333)% gave significant value (sig*) below than 0.05. Optimal formula proved that SNEDDS can significantly increase mefenamic acid dissolution of pH 7.4 (ileum fluid). The optimal formula of mefenamic acid SNEDDS successfully formed an uniformity droplet size (PDI 0.18) with mean size 241.9 nm and the surface charge has a value of -16.5 mV respectively.